The effect of people, process, and physical evidence on customer satisfaction - Rionando, Rionando; Wadud, Muhammad (Enrichment : Journal of Management, 2023)
This study aims to determine whether people, process, and physical evidence affect customer satisfaction at a private bank in the city of Palembang. This type of research is quantitative. The population is 1500 customers with a sample of 100 respondents using accidental sampling. Data analysis techniques used descriptive statistical tests, instrument quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the study stated that people, process, and physical evidence had an effect on customer satisfaction at one of the private banks in the city of Palembang.